CONTEXTUAL BASIC CHEMISTRY MODULE DEVELOPMENT FOR BIOLOGY STUDENTS WITH DIVERSE ABILITIES: AN INCLUSIVE AND DIFFERENTIATED LEARNING APPROACH - Rizki, Cut Novrita; Helmanda, Cut Mawar; Fajriana, Nurul (Chimica Didactica Acta, 2025)
This study explores the design and development of a contextual basic chemistry module specifically tailored to meet the diverse academic needs of undergraduate biology students. Recognizing the varying educational backgrounds and learning styles of students, the module was systematically created using the ADDIE instructional model, incorporating principles of inclusive pedagogy and differentiated instruction. To enhance accessibility and relevance, the module's content was closely linked to biological concepts and enriched with diverse features such as visual aids, interactive elements, and tasks structured at multiple levels of difficulty. The module was evaluated through a limited-scale implementation involving 25 students from the Tadris Biology program at Muhammadiyah University Aceh, who participated as respondents. Results from this implementation indicated notable improvements in students engagement, conceptual understanding of chemistry, learning motivation, and autonomy. These findings underscore the effectiveness of contextual and inclusive teaching strategies in fostering equitable learning environments and addressing conceptual gaps in interdisciplinary education, particularly for biology students navigating foundational chemistry topics.